2005
DOI: 10.1128/jvi.79.4.2484-2492.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Proteolytic Cleavage of Gag Proteins in Budded Simian Immunodeficiency Virus

Abstract: Gag and several of its cleavage intermediates likely precedes the cleavage of these domains by the viral protease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…If we presume that the HIV IRES-driven Pr55 Gag isoforms function similarly to SIV p43 to suppress intracellular cleavage of Pr55 Gag , the difference in replication kinetics may be reconciled simply by comparing the processing of Pr55 Gag in budded HIV-1 and SIV virions. In this study and an earlier report, we demonstrate that processing of SIV Pr55 Gag can occur over time in budded virions (Rue et al, 2005). However, in HIV-1 it is not clear whether intravirion processing of Pr55 Gag occurs; one study suggested that processing of Pr55 Gag occurred either before the virion was released from the cell, or very shortly after budding (Kaplan, Manchester, and Swanstrom, 1994).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…If we presume that the HIV IRES-driven Pr55 Gag isoforms function similarly to SIV p43 to suppress intracellular cleavage of Pr55 Gag , the difference in replication kinetics may be reconciled simply by comparing the processing of Pr55 Gag in budded HIV-1 and SIV virions. In this study and an earlier report, we demonstrate that processing of SIV Pr55 Gag can occur over time in budded virions (Rue et al, 2005). However, in HIV-1 it is not clear whether intravirion processing of Pr55 Gag occurs; one study suggested that processing of Pr55 Gag occurred either before the virion was released from the cell, or very shortly after budding (Kaplan, Manchester, and Swanstrom, 1994).…”
Section: Discussionsupporting
confidence: 54%
“…Proteolytic processing of Pr55 Gag in budded virions was carried out as previously described (Rue et al, 2005). Briefly, 293T cells were transfected as described above with proviral DNA for either WT SIVmac239 or SIVmac239 p43(-) and labeled with [ 35 S]Met/Cys as described above, except for only 1 h. Virus-containing supernatants were filtered, aliquoted, and incubated at 37ºC for different periods of time.…”
Section: Analysis Of Proteolytic Processing Of Pr55 Gag In Budded Virmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether it might be taking part in the cleavage of the VP7 still need further investigation. Approximately 5% of gag gene (such as lentiviruses, human immunodeficiency virus, simian immunodeficiency virus) produced other proteins causing by the ribosomal frameshift with independent functions (Rue, Roos, Tarwater, Clements, & Barber, 2005). Two mechanisms for generating more than one protein from a single mRNA have been reported.…”
Section: Tablementioning
confidence: 99%